Analisis Tarif Jalan Tol Yogyakarta–Bawen Berdasarkan Sensitivitas Volume Lalu Lintas Terhadap Perubahan Tarif - Teguh Wisanggeni; Russ Bona Frazila; Taufiq Suryo Nugroho (Jurnal Teknik Sipil, 2025)
Abstract Determining toll road rates is an important factor for the sustainability of investment and optimal benefits for users. This study analyzes the sensitivity of traffic volume to rate changes on the Yogyakarta–Bawen Toll Road using secondary data from PT Jasa Marga (Persero) Tbk and PT Jasamarga Jogja Bawen. The methods used include Ability to Pay (ATP) and Willingness to Pay (WTP) determination, time value determination, and macro transportation modeling with PTV Visum. The results show that an increase in toll rates reduces traffic volume, but there is an optimum point that generates maximum revenue. The optimal toll rates for Class I vehicles is projected to be IDR 1,400/km in 2029 and IDR 2,130/km in 2039, assuming that the time value follows inflation. These findings indicate that higher toll rates during the initial operational phase do not necessarily result in maximum toll revenue, thus requiring periodic evaluation of the toll setting policy. Keywords : Toll road, toll rate, traffic volume sensitivity, toll revenue, traffic modelling.